Plan de reforestación en las áreas de conservación y uso sustentable municipal “Río Coaque” del cantón Pedernales - Ormaza Zambrano, Deivy José (2025)
This research was carried out with the objective of developing a Reforestation Plan in the “Río Coaque” Municipal Conservation and Sustainable Use Areas (ACUS) of Pedernales canton, Manabí province. To achieve this, techniques such as interviews and surveys were used to facilitate the collection of key data from the study area. As part of the process, the current status of the ACUS was diagnosed to establish an environmental baseline. Priority areas for reforestation were identified within these zones, in order to carry out their ecological restoration through the use of native forest species. Based on this diagnosis, a Reforestation Plan was designed, aimed at conserving the region's forest ecosystems. The results revealed that this area faces several environmental challenges that require immediate attention, as well as specific measures to ensure its sustainability and the recovery of its forests. Through interviews, the most urgent areas for reforestation were identified, considering factors such as soil degradation and connectivity with other protected areas—representing a key strategy to maximize ecological benefits. Based on these findings, the Reforestation Plan was implemented with the purpose of strengthening the restoration of degraded areas of the ACUS due to human activities, with a focus on conservation and sustainable development. It is concluded that community participation is essential to improve engagement in reforestation efforts and the sustainable management of forests.